(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Latvia and Belarus are small countries with limited scope of natural resources. However, the available mineral resources play important role in production of mineral products for domestic and foreign consumption. Main goal of the paper is to characterize the role of extraction industry in national economy and mineral products trade in two neighboring countries - Latvia and Belarus. To achieve the goal, the role of mining and quarrying industry in Latvia and Belarus was identified; trade of mineral resources in Latvia was analyzed. The main trends in the development of its own mineral resources of the Republic of Belarus were identified, the role of mineral resources in the commodity structure of foreign trade of the Republic of Belarus was shown, ways to increase the level of security of the country's own organic and mineral resources were determined, including the improvement of the legal framework. The research was performed in 2012; the following methods were used in the paper: comparative analysis and synthesis, statistical analysis and monographic methods.